Concept of a Fuel Injector Control System Based on Electric Current Signals in OBD - POŁANIECKI, Adrian; SZOST, Kinga; MĄCZAK, Jędrzej (Engineering Transactions, 2025)
This work presents a concept for controlling the injectors of internal combustion engines. It is possible to observe electric current signals with high repeatability on the coil of fuel injectors. Mechanical changes observed in these signals indicate the presence of certain anomalies, allowing for fault detection. A precise analysis of characteristic points in the signal enables diagnosing the injector’s condition in the next control loop. The analysis of characteristic values in such signals has demonstrated the possibility of diagnosing fuel injectors under normal operating conditions. For this purpose, an additional measurement system must be connected to the injector, along with the implementation of algorithms on a controller to process the recorded data samples. These data could improve dosing precision by improving the understanding pf the injection process itself. Knowing the precise beginning and end of the injection process as well as ensuring proper injector function, allows for an accurate determination of the fuel dose injected into the combustion chamber and the detection of any potential damages. This concept could lead to a better understanding of the injection process and enhance combustion process, which can potentially reduce emissions of harmful substances in exhaust gases.